Long non-coding RNA regulating androgen receptor signaling in breast and prostate cancer. (28th April 2021) - Kumar, Shashank; Prajapati, Kumari Sunita; Singh, Atul Kumar; Kushwaha, Prem Prakash; Shuaib, Mohd; Gupta, Sanjay
Abstract: The human genome transcribe an array of RNAs that do not encode proteins and may act as mediators in the regulation of gene expression. Long non-coding RNAs (lncRNAs) are a group of non-coding RNAs consisting of more than 200 nucleotides of RNA transcripts that play important role in tumor development. Numerous lncRNAs have been characterized as functional transcripts associated with several biological processes and pathologic stages. Although the biological function and molecular mechanisms of lncRNAs remains to be explored, recent studies demonstrate aberrant expression of several lncRNAs linked with various human cancers. The present review summarizes the current knowledge of lncRNA expression patterns and mechanisms that contribute to carcinogenesis. In particular, we focus on lncRNAs regulating androgen receptor signaling pathways in prostate and breast cancer subtype having prognostic and therapeutic implications. Highlights: lncRNAs regulate notable cellular and physiological processes. lncRNA regulate androgen receptor signaling in prostate and breast cancer subtypes. lncRNAs contribute to anti-androgen resistance in TNBC and prostate cancer. lncRNAs are of prognostic/therapeutic significance in breast and prostate cancer.